Prevalence of Low Birth Weight and Gestational Maturity Associated with Trichomonas vaginalis Infection in Pregnant Women - Nadyah Haruna; Esa Lestari; Syafri Syafri; Nildawati Nildawati (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Trichomonas vaginalis is a sexually transmitted protozoan known to contribute to adverse pregnancy outcomes, including low birth weight (LBW) and preterm birth. In Indonesia, where routine screening for this infection is limited, the relationship between T. vaginalis and neonatal health outcomes remains inadequately explored. Objective: This study aims to evaluate the correlation between PCR-confirmed T. vaginalis infection and neonatal outcomes, particularly birth weight and gestational maturity, among pregnant women presenting with pathological vaginal discharge. Methods: A cross-sectional study was conducted involving 167 pregnant women attending antenatal care. Sociodemographic and clinical data were recorded. Vaginal swabs were collected and analyzed using polymerase chain reaction (PCR) to detect T. vaginalis. Neonatal outcomes, including birth weight and gestational age, were assessed post-delivery. Bivariate analysis using Cramér’s V was performed to examine the strength of the association between infection status and outcomes. Results: Out of 167 participants, 85 (50.9%) tested positive for T. vaginalis. Most infected women were between 20–35 years old (76.5%), from low-income households (55.3%), and had only primary education (71.8%). Among PCR-positive mothers, 20% delivered low-birth-weight infants, compared to 4.9% in the PCR-negative group (Cramér's V = 0.210), indicating a moderate correlation. Preterm births occurred in 16.5% of PCR-positive cases, compared to 9.8% among those who were negative (Cramér's V = 0.082), suggesting a weak association. Conclusion: T. vaginalis infection during pregnancy is moderately associated with LBW and weakly associated with prematurity. These findings support the need for routine T. vaginalis screening during antenatal care to minimize neonatal complications related to untreated infections; however, given the cross-sectional design, causal inferences cannot be established."